Raising of Chir (Pinus roxburghii) Plantations in Himachal Pradesh - Singh, R. V. (Indian Forester, 1970)
The need and possibilities of raising industrial plantations of chir in Himachal Pradesh have been discussed. Raising of chir seedlings in polythene bags and then planting them in the field has proved to be the best method of raising chir artificially. Results of trials of different sizes of polythene bags and of different sizes of pits have been summarised. The cost of different operations involved in raising chir plantations has also been given.